The Gender of Photography : How Masculine and Feminine Values Shaped the History of Nineteenth-Century Photography - Hudgins, Nicole (Bloomsbury Publishing USA, 2020)
"It would be unthinkable now to omit early female pioneers from any survey of photography's history in the Western world. Yet for many years the gendered language of American, British and French photographic literature made it appear that women's interactions with early photography did not count as significant contributions. Using French and English photo journals, cartoons, art criticism, novels, and early career guides aimed at women, this volume will show why and how early photographic clubs, journals, exhibitions, and studios insisted on masculine values and authority, and how Victorian women engaged with photography despite that dominant trend. Focusing on the period before 1890, when women were yet to develop the self-assurance that would lead to broader recognition of the value of their work, this study probes the mechanisms by which exclusion took place and explores how women practiced photography anyway, both as amateurs and professionals. Challenging the marginalization of women's work in the early history of photography, this is essential reading for students and scholars of photography, history and gender studies."--